Suicidal Adolescents and the Greek Community of Montreal - Savides, Danae (Études helléniques / Hellenic Studies, 2015)
This study examines the phenomenon of Greek adolescent suicide and familial reactions to this amongst members of the Greek Community of Montreal. Interpretation of the data revealed the following the social stigma attached to suicide is more pronounced in the Greek community than in the larger population. This is because of the influence of religious ideology, societal attitudes and the particular importance Greek society places on family and parental roles. Greek families are more resistant to treatment. This article is based on the Master of Social Work Thesis deposited at McGill University, August 1995